Optimizing Pricing and Digital Marketing to Strengthen Consumer Loyalty in Startupreneur: Optimalisasi Harga dan Digital Marketing untuk Meningkatkan Loyalitas Konsumen Startupreneur - Sunarya, Po Abas; Mustopa, Muhamad Ikhsan; Julianingsih, Dwi; Bibils, Natalie; Hua, Chua Toh (ADI Publisher, 2025)
In the digital economy era, consumer loyalty has become a strategic asset for startupreneurs operating amid dynamic competition and information dense markets. This study examines the integrative role between pricing strategies based on Behavioral Economics principles and digital marketing approaches in shaping and enhancing consumer loyalty. Techniques such as anchoring price, scarcity marketing, bundling, and framing are synergistically combined with digital marketing tactics including social media utilization, content personal ization, and micro influencer engagement to create more resonant and recur ring consumer experiences. Through a qualitative method based on litera ture studies and observations of several digital startups in Indonesia, this study finds that ethical price optimization and adaptive digital campaigns not only drive short-term conversions but also build customer trust and retention in the long term. These findings indicate that strategies rooted in consumer behavior understanding and supported by digital marketing technology can serve as an important catalyst for the sustainable growth of startupreneurs. Recommendations are formulated to encourage the implementation of strategies that are not only market-competitive but also aligned with transparency, sustainability, and modern business ethics. The novelty of this study lies in its integrative approach, combining behavioral-based pricing strategies with digital marketing techniques to build consumer loyalty among startupreneurs. This approach remains under explored in the context of startups in developing countries, particularly Indonesia, and thus offers a fresh perspective for sustainable digital business models.